Healthcare and Compassion: Towards an Awareness of Intersubjective Vulnerability; Comment on "Why and How Is Compassion Necessary to Provide Good Quality Healthcare?" - Kate Kenny (Kerman University of Medical Sciences, 2015)
How to instill compassion in a healthcare organization? In this article, I respond to Marianna Fotaki's proposals in her piece, 'Why and how is compassion necessary to provide good quality healthcare?' by drawing on insights from organization studies. Following Fotaki, I argue that to instill targets and formal measures for assessing compassion would be problematic. I conclude by drawing on psychoanalytic and feminist theories to introduce alternatives, specifically proposing an approach that is grounded in a shared sense of a common, embodied precarity, which necessitates our commitment to preserving the conditions in which life might flourish.